Female genital cutting: current practices and beliefs in western Africa - Heather L Sipsma; Peggy G Chen; Angela Ofori-Atta; Ukwuoma O Ilozumba; Kapouné Karfo; Elizabeth H Bradley (Bulletin of the World Health Organization, 2012)
OBJECTIVE: To conduct a cross-national comparative study of the prevalence and correlates of female genital cutting (FGC) practices and beliefs in western Africa. METHODS: Data from women who responded to the Multiple Indicator Cluster Surveys between 2005 and 2007 were used to estimate the frequencies of ever having been circumcised, having had a daughter circumcised, and believing that FGC practices should continue. Weighted logistic regression using data for each country was performed to determine the independent correlates of each outcome. FINDINGS: The prevalence of FGC was high overall but varied substantially across countries in western Africa. In Sierra Leone, Gambia, Burkina Faso and Mauritania, the prevalence of FGC was 94%, 79%, 74% and 72%, respectively, whereas in Ghana, Niger and Togo prevalence was less than 6%. Older age and being Muslim were generally associated with increased odds of FGC, and higher education was associated with lower odds of FGC. The association between FGC and wealth varied considerably. Burkina Faso was the only country in our study that experienced a dramatic reduction in FGC prevalence from women (74%) to their daughters (25%); only 14.2% of the women surveyed in that country said that they believe the practice should continue. CONCLUSION: The prevalence of FGC in western Africa remains high overall but varies substantially across countries. Given the broad range of experiences, successful strategies from countries where FGC is declining may provide useful examples for high-prevalence countries seeking to reduce their own FGC practices.